Mot destinationer i världsklass: från materiella till immateriella värden inom destinationsutveckling och Strategi 2020 : En forskningsöversikt om hur immateriella värden kan göra destinationer konkurrenskraftiga - Enström, Josefin; Rex, Amanda (2013)
The study is conducted as a thesis for a bachelor's degree in the program of Experience Production at Luleå University of Technology.The study involves destination development, Strategy 2020 and the intangible values in experience production. Strategy 2020 is developed by Svensk Turism AB as a basis for destinations to work with. The background to the study is based on the experience society and the experience economy. We have identified that people in the experience society today requires more than the basic needs and material values meanwhile the competition for destinations increases with globalization and urbanization. It is thus necessary to identify the destinations’ unique offerings by intangible values that add meaning to people's lives and satisfies their needs.The purpose of this study is to investigate whether the Swedish tourism industry can benefit from intangible values in order to in the purpose of destination development reach Strategy 2020. We have responded to the study's research questions by a qualitative research study that is made with a positivistic and deductive approach.We have through a selection of theories arrived at our results, featuring six experience production theories all of which concern the intangible values. Each of the theories have been analyzed where the results show that five of the theories could be applied to the theory The Six Senses. These theories along with the general concepts of tourism and destination development go, stay, eat and do have been shaped as a tool for actors within destination development. We thereby recognize that destination development can benefit from intangible values. Validerat; 20130626 (global_studentproject_submitter)